The performance of surfactant mixtures at low temperatures - Liley, JR; Penfold, J; Thomas, RK; Tucker, I; Petkov, J; Stevenson, P; Banat, IM; Marchant, R; Rudden, M; Webster, J (Elsevier, 2019)
Optimising detergency at lower temperatures is of increasing interest due to environmental and economic factors, and requires a greater understanding of the effects of temperature on the adsorption of surfactant mixtures at interfaces. The adsorption properties of surfactant mixtures and biosurfactant/surfactant mixtures have been studied at room temperatures and at temperatures below ambient using surface tension and neutron reflectivity measurements. For the ternary surfactant mixture of octaethylene monododecyl ether, C12E8, sodium dodecyl 6-benzene sulfonate, LAS, and sodium dioxyethylene glycol monododecyl sulfate, SLES, the surface tension at the air-water interface increases with decreasing temperature. In contrast, there is a notable reduction in the increase in the surface tension with a decrease in temperature from 25 °C to 10 °C for the 5 component rhamnolipid/surfactant mixture of the mono-rhamnose, R1, and di-rhamnose, R2, with C12E8/LAS/SLES. The associated neutron reflectivity data for the ternary C12E8/LAS/SLES mixture and the significant observation is that the 3, 4, and 5-component mixtures containing rhamnolipids in conjunction with the other surfactants show changes in composition and adsorbed amounts of the individual components which are close to the experimental error. However the significant observation is that the neutron reflectivity data indicate that the improved surface tension tolerance at lower temperatures is associated with the dominance of the rhamnolipid adsorption in such mixtures. Hence the introduction of the rhamnolipids provides a tolerance to the adverse effects associated with reduced temperatures, and a potential for improved detergency at relatively low temperatures.